Emerging practices in international development evaluation - Donaldson, Stewart I.; Azzam, Tarek; Conner, Ross F. (Evaluation and society., 2013)
The impetus for this volume comes from reflecting on many years of experience, successes and failures in development evaluation in Asia and Africa, and from recent work supported by the Rockefeller Foundation on Rethinking, Reshaping, and Reforming Evaluation. The concepts, frameworks and ideas presented in this volume are a useful contribution to the ongoing efforts at rethinking, reforming and reshaping international development evaluation. They come from leading thinkers and practitioners in development, evaluation, research and academia who have recognized that development evaluation must evolve if it is to respond to the challenges of the 21st Century and play a meaningful role in social and economic transformation. This volume will be of great interest to evaluation scholars, practitioners, and students, particularly to those interested in international development projects, programs, and policies. This book will be appropriate for a wide range of courses, included Introduction to Evaluation, International Development Evaluation, Program Evaluation, Policy Evaluation, and evaluation courses in International Development, International Relations, Public Policy, Public Health, Human Services, Sociology, and Psychology.